IMPACT OF DISABILITY ON THE FAMILY - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper investigates "Impact of disability on the family", which aimed to determine the impact of care of a disabled patient on the family, a systematic review of 38 articles that were the result of the search in databases such as SCOPUS, EBSCO HOST and GOOGLE SCHOOL. The information obtained was ordered and synthesized into double-entry tables to then be selected or discarded. Subsequently, extracts of the method, results, discussion, conclusions and limitations of 12 relevant investigations were placed in the study case. As a result it was found that the majority are Inferential descriptive studies, where 50% have studied the impact of various diagnoses, also 59% have considered in the sample parents the rest represents 61%, being in the studies stress and the lack of quality of life in the mother and father, the support they receive is not enough, there are expectations from parents about availability of the service. As a conclusion, the search for the greatest amount of information on the study topic was completed, finding that 25% are Inferential Descriptive Research, 17% Econometric Method, 18% (9% Inductive, 9% Qualitative Descriptive) and 8% respectively for Narrative, Qualitative, Case Study, Theoretical and Descriptive Debate. It has also been possible to determine that stress in the mother and father affects their quality of life, the representative samples selected have been mother and father. As limitations in studies, parental volunteering to participate in studies prevails and it is recommended to deepen research on family expectations towards providers, further development in terms of policy, improvements in FQOL and resilience